Effect of specimen notch quality on the essential work of fracture of ductile polymer films. (July 2017) - Martínez, A.B.; León, N.; Segovia, A.; Cailloux, J.; Martínez, P.P.
Highlights: The notch quality drastically affects the EWF behaviour and parameters. The notch tip radius affects the shape of the stress-displacement curves. The plastic deformation ahead of the crack tip affects the stress-displacement curves. Femtolaser ablation technique provides repetitive good quality notches. Abstract: The essential work of fracture approach has been employed to analyse the effect of notch sharpening on the fracture toughness of a semicrystalline multiphase ethylene-propylene block copolymer. Double edge notched tension specimens were sharpened using different techniques: femtolaser ablation, razor blade sliding at room and liquid nitrogen temperatures, saw cutting, plastically deformed saw cutting, and scalpel sliding. The notch sharpening techniques provide notches of different quality in relation to both the notch tip radius and the plastic deformation in front of the crack tip. The best quality notches were produced by the femtolaser ablation technique, which provides very sharp notches without plastic deformation ahead of the crack tip. The effects of the non-collinearity of the notches and tilted specimens on the testing machine grips were also analysed. The shape of the registered stress–displacement curves shows differences, but only in the range comprised between the displacements corresponding to the maximum stress and the onset of crack initiation. A larger crack tip radius and/or larger extent of plastic deformation in front of the notch root leads to larger values of the displacement at the onset of crack initiation, resulting in higher values for the specific essential work of fracture. Yet on the other hand, the values of the slope of the essential work of fracture plot remain unchanged. A lower value for the specific essential work of fracture was obtained for the specimens sharpened using the femtolaser ablation technique.